Biohydrogen Production from Organic Waste – A Review - Sampath, P.; Brijesh; Reddy, Kakarla Raghava; Reddy, C. Venkata; Shetti, Nagaraj P.; Kulkarni, Raghavendra V.; Raghu, Anjanapura V. (Chemical engineering & technology, 2020)
Hydrogen fuel is a promising alternative to fossil fuels because of its energy content, clean nature, and fuel efficiency. However, it is not readily available. Most current producion processes are very energy intensive and emit carbon dioxide. Therefore, this article reviews technological options for hydrogen production that are eco‐friendly and generate clean hydrogen fuel. Biological methods, such different fermentation processes and photolysis are discussed together with the required substrates and the process efficiency. As an alternative to fossil fuels, hydrogen fuel is eco‐friendly and very efficient. However, its production is currently still very energy‐intensive and increase CO2 emissions. This review discussed biological production technologies, such as photolysis and various fermentation methods, as eco‐friendly options.